Cost-Effectiveness Analysis for the Treatment of Hyperphosphatemia in Predialysis Patients: Calcium-Based versus Noncalcium-Based Phosphate Binders - B. L. Goh; A. Soraya; A. Goh; K. L. Ang (International Journal of Nephrology)
Background. Hyperphosphatemia in chronic kidney disease (CKD) patients is often treated with calcium carbonate (CaCO3) despite the fact that CaCO3 is associated with increased calcium load and potentially increased cardiovascular risk. Alternative treatments with noncalcium-based phosphate binders do not increase the calcium load but are more costly. This study analyzes the cost-effectiveness of sevelamer versus CaCO3 for the treatment of hyperphosphatemia in stage III-V predialysis CKD patients in Malaysia. Methods. A Markov decision model was adapted to simulate a hypothetical cohort of CKD patients requiring treatment for hyperphosphatemia. Survival was estimated by using efficacy data from the INDEPENDENT-CKD clinical trial. Cost data was obtained from Malaysian studies while health state utilities were derived from literature. Analysis was performed over lifetime duration from the perspective of the Ministry of Health Malaysia with 2013 as reference year. Results. In the base case analysis, sevelamer treatment gained 6.37 life years (5.27 QALY) compared to 4.25 life years (3.54 QALY) with CaCO3. At 3% discount, lifetime costs were RM159,901 ($48,750) and RM77,139 ($23,518) on sevelamer and CaCO3, respectively. Incremental cost-effectiveness (ICER) of sevelamer versus CaCO3 was RM47,679 ($14,536) per QALY, which is less than the WHO threshold of three times GDP per capita (RM99,395) per QALY. Sensitivity analyses, both using scenario sensitivity analysis and probabilistic sensitivity analysis, showed the result to be robust. Conclusions. Our study finds that sevelamer is potentially cost-effective compared to CaCO3, for the treatment of hyperphosphatemia in predialysis CKD III-V. We propose that sevelamer should be an option in the treatment of Malaysian predialysis patients with hyperphosphatemia, particularly those with high calcium load.